Learning in the World of Information and Communication Technology through Online Videos: Developing the Ability to Edit videos for Teaching of Lecturers at Souphanouvong University - sisombath, sithonh; Xaychalern, Kongkeo; Thipphaphone, Kinnaly; Buolakham, Sengdala; PANFONGPHET, Sipaseuth (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research study is to improve the basic skills of teaching video media production of teachers, to find problems in the production of teaching video media of Lecturers and to find factors that can motivate Lecturers to produce more of their own teaching video media. Findings revealed that lecturers significantly improved their basic skills in recording, editing, and website creation, achieving nearly 100% proficiency post-training. The Problems found that inadequate computer specifications (66.66%), slow internet connections (38.88%), and a lack of foundational computer knowledge (55.55%). These issues hindered effective practice, highlighting the need for better resources. The research also identified key motivational factors for lecturers, including access to fast, high-quality internet, the requirement for subject-specific teaching videos, and financial support for video production. These factors demonstrated a statistically significant correlation with lecturers' motivation to create and share educational content. Overall, the study underscores the importance of training and resource availability in fostering digital education and identifies specific barriers and motivators that can enhance lecturers' engagement with technology in teaching.